Determination of the applicability of SERVQUAL as an assessment tool at the Leslie Hardinge Library - Siapco, Elizabeth J.; Faderon, Rosalie B.; Santos, Herminia H.; Fonseca, Soledad J. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2006)
SERVQUAL is a service quality assessment tool used in most marketing related research activities. A few validations have been conducted in the past to determine the applicability of SERVQUAL in foreign libraries. There has been no similar validation attempted in Philippines libraries.
The purpose of the study was to determine the applicability of SERVQUAL as a service quality assessment tool at the Leslie Hardinge Library.
The study attempted to answer two main points of the research: 1. Is the SERVQUAL a reliable and valid tool in assessing service quality at the LHL?. 2. What is the gap between user expectations and perception of service quality at the LHL as measured by SEVQUAL?
This validation research shows that SERVQUAL is a reliable tool in assessing service quality at the LHL as shown by the high internal consistency of its constructs/dimensions. However, these constructs/dimensions failed to indicate the three-factor solutions namely: affect of service, presentation of service, service competence produced from principal axis factoring. This indicates that in the context of a library, specifically the LHL, the original constructs/dimensions may not be valid in characterizing such service quality assessment.
All the items and original dimensions of SERVQUAL were perceived to be lower than what are expected of an ideal library. Of the original constructs/dimensions, tangibles and reliability had the highest gaps, an indication that users expect more acquisitions, improvement in equipment, and more dependable service.
In the light of the findings, the following recommendations were presented: 1. There should be a regular self-evaluation to assess the level of service quality among LHL personnel. 2. There must be a continual feedback assessment from its users, namely the students and faculty. 3. The administration must see to it that the quality of future personnel should be assessed carefully. 4. There should be a series of plans and implementing programs to improve the quality of service at the Leslie Hardinge Library. 5. There should be a constant investigation to know what aspects of study are needed to improve the quality of service in the library. 6. Actively promote goodwill among its personnel.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Information services -- Philippines -- Cavite